ESL UNDERGRADUATES’ PERCEPTIONS OF TEACHER SELF-DISCLOSURE IN A MALAYSIAN WRITING CLASSROOM - Paul GnanaSelvam Pakirnathan; S. Maartandan Suppiah; Napisah Kepol (MOJES: Malaysian Online Journal of Educational Sciences, 2021)
Past studies have indicated that teachers’ self-disclosure has a direct influence on students’ learning. It has impacted students’ motivation, participation, interest, affect for teacher and course, solidarity, affinity seeking behaviours and out-of-classroom communication. However, little is understood about how this phenomenon affects teaching and learning across different cultural contexts and ESL environments. This study attempted to investigate ESL teachers’ self-disclosures in a Malaysian writing classroom. Fifty second-year undergraduates enrolled in an academic writing course and the respective teacher were interviewed using semi-structured interview protocols. The thematic analysis indicated that seven themes, learning strategy, writing strategies, content generating strategies, affective learning, teacher-student communication, classroom climate and appropriateness were important factors that influenced teachers’ self-disclosures in the ESL writing classroom. The results from this study demonstrate that ESL students’ perceptions towards teachers’ self-disclosure have important implications for affective, instructional and learning strategies. This study concludes that teachers’ self-disclosure has potential use as a pedagogical tool that could enhance the teaching and learning of ESL writing.